2003
DOI: 10.1037/0735-7044.117.3.606
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory thalamus lesions eliminate successive negative contrast in rats: Evidence against a memory deficit.

Abstract: Successive negative contrast is the exaggerated reduction of licking that occurs when rats expecting a high-value reward are given a low-value reward. This effect is typically investigated with a 24-hr retention interval between access periods. The present experiment tested the hypothesis that the absence of successive negative contrast in rats with bilateral lesions of the gustatory thalamus (GT) is due to a memory deficit. The results argue against this hypothesis by showing that, irrespective of retention-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Groups included in the behavioral analysis were: SHAM-Saline (n = 11), SHAM-Morphine (n = 10), GTX-Saline (n = 8), and GTX-Morphine (n = 8). GT Lesions in the current study were comparable in size and locus to those in our earlier work (e.g., [58,49,53,54]).…”
Section: Methodssupporting
confidence: 84%
“…Groups included in the behavioral analysis were: SHAM-Saline (n = 11), SHAM-Morphine (n = 10), GTX-Saline (n = 8), and GTX-Morphine (n = 8). GT Lesions in the current study were comparable in size and locus to those in our earlier work (e.g., [58,49,53,54]).…”
Section: Methodssupporting
confidence: 84%
“…In support of this, rats with lesions of the gustatory thalamus not only fail to demonstrate an ACE but also a successive negative contrast effect that occurs when intact rats are unexpectedly shifted from a greater to a lesser reward (40,42,43). In this case, intake of the lesser 0.15% saccharin reward is reduced in the lesioned rats when downshifted from a 1.0 M sucrose solution, but only to the level of the unshifted saccharin controls (42).…”
Section: Discussionmentioning
confidence: 56%
“…The successive negative contrast effect, on the other hand, is a multistage phenomenon that depends upon comparing an available level of reward (4% sucrose or 0.15% saccharin) with the memory of a preferred sucrose reward (32% or 1.0 M sucrose) that was received 24 h earlier. A simple short-term/long-term memory distinction, however, likely will not account for the dissociation in the lesion data, as Reilly and Trifunovic (43) showed that thalamic lesions disrupted successive negative contrast effects even when the downshift occurred only 7.5 min (rather than 24 h) after the final access period to the preferred 1.0 M sucrose reward, and simultaneous negative contrast effects, in turn, remain intact in THLX rats even when as much as 8 min elapsed between alternating access periods to the two disparate levels of reward within a given daily session (38).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The thalamic relay for tongue taste, thermal, and tactile sensibility, however, had little influence on the same three tasks when rewarded by either sucrose or corn oil. Somewhat more medial thalamic taste area lesions had no effect on preference tests, CTA, or Na-appetite [24, 27, 33], but did block ACE and successive negative contrast effect [24, 25, 35]. The results did not support our hypothesis that the TOA is necessary for oil reward, but indicated that the TOA might process sucrose and oil differently.…”
Section: Discussionmentioning
confidence: 63%